Once upon a time in China III : "a hero beyond all others" - Tsui, Hark (Quezon City : Magnavision.)
World-wide superstar Jet Li (Romeo Must Die Lethal Weapon 4) kicks into action when he reprises his role as martial arts master Wong Fei-Hung. When he and his trusted sidekick Chung arrives in Peking, they're just in time for the Empress-sponsored Lion King martial arts contest. But first, Wong Fei-Hung must win back his secret love, Yee, from the nefarious Russian diplomat turned spy Tumanovsky, who has a secret plan to assassinate the President.Now fists and feet will fly as Wong Fei-Hung tries to foil the assassination attempt, defeat his awesome rival, Thunder Foot, triumph over the untrustworthy Leung Fun and win the Lion King contest in this gravity-defying, non-stop action adventure.